Modern Trends in Lexicography - Nashirova Shakhnoza Burievna (Academia One Publishing, 2023)
The contemporary period in the development of the lexicography of the English language can be called "scientific or historical", since it is based on the following concepts: 1) compilation of dictionaries according to the historical principle
Keywords: compilation; historical; lexicography